Treatment for oral squamous cell carcinoma: Impact of surgeon volume on survival. (September 2019) - Liu, Timothy; David, Michael; Ellis, Owen; (Hubert) Low, Tsu-Hui; Palme, Carsten E.; Clark, Jonathan; Batstone, Martin
Highlights: Patients with oral squamous cell carcinoma treated by high-volume surgeons have significantly improved outcome in both disease control and mortality. Different surgical access techniques and reconstructive approaches showed minimal impact on patient survival in the treatment of oral squamous cell carcinoma. Minimum of performing 20 oral squamous cell carcinoma ablations per annum is recommended for head and neck surgeons to maintain competency in the surgical management of these patients. Abstract: Background: The volume-outcome relationship is a well-known phenomenon in surgical oncology. The aim of this study was to quantify the impact of surgeon volume on the treatment outcome of oral squamous cell carcinoma (OSCC) patients. Methods: All new OSCC cases treated with curative intent between 2008 and 2013 were included. A heterogeneous set of predictor variables was collected, including patient, tumour and treatment factors. The outcomes of interest were recurrence-free survival (RFS), overall survival (OS) and disease-specific survival (DSS). To investigate the cut-off in surgeon volume, the number of OSCC resections was analysed in multiplies of 5 cases per annum according to DSS, using univariable regression analysis. Results: 534 cases were recruited. Independently, the negative predictors for patient survival were age, perineural invasion, worsening tumour staging, and extracapsular spread. High-volume surgeon was determined to be most significant at 20 cases per annum and significantly associated with improved RFS (HR: 0.67), OS (HR: 0.44), and DSS (HR: 0.39). Conclusions: Results from this study support the rationalisation of OSCC management at high-volume centres and in the hands of experienced surgeons for better patient survival. Head and neck surgeons should perform a minimum of 20 OSCC cases per year to maintain competency in OSCC ablation.